Analisis Implementasi Pemberdayaan Usaha Ekonomi Mikro Kecil dan Menengah (UMKM) - Sukesi, . (Kajian Manajemen dan Bisnis, 2009)
To speed up economy restoration with brace development basement sustainability and with justice based on in democracy economy system. Done to pass development at economy area with development at Natural Resources (SDA) and environment. Make use wealth SDA without neglecting principles sustainability q1rd environment preservation.